Imaging features of disseminated xanthogranulomatous inflammation in eclectus parrots (Eclectus roratus). Issue 4 (20th May 2020) - Hanson, Melissa E.; Donovan, Taryn A.; Quesenberry, Katherine; Dewey, Amanda; Brown, Cindy; Chen, Sue; Le Roux, Alexandre B.
Abstract: Xanthogranulomatous disease is a rare condition, which can be caused by infection, inflammation, hemorrhage, immunologic disease, or inherited lysosomal disorders. It is characterized by non‐intracellular lipid and cholesterol deposits among an inflammatory infiltrate of vacuolated macrophages and giant cells. The diagnosis of xanthogranulomatous disease is challenging, with nonspecific imaging findings often misinterpreted as aggressive neoplastic processes in humans. In this retrospective case series study, we describe the diagnostic imaging characteristics of a disseminated xanthogranulomatous condition identified in five eclectus parrots ( Eclectus roratus ). Decreased serosal detail and celomic distension were present in all three birds radiographed, with multifocal variably sized celomic mineralization (3/3 birds), and extracelomic mineralized masses (1/3 birds). Celomic effusion with foci of celomic mineralization and hepatomegaly were identified in all birds (3/3) imaged with ultrasound. Finally, a mineralized mural ventricular mass was present in one of three patients imaged with CT, multifocal celomic mineralization with moderate to severe celomic effusion in two of three patients, diffuse severe proventricular and intestinal dilation in all three patients, and atherosclerosis of the major arterial trunks in all three patients. Veterinary radiologists should be aware of this inflammatory condition in birds, especially in eclectus parrots, and should be able to recognize the imaging features of xanthogranulomatous inflammation.